(3TQM MceI GdYjfs - (3eMeO Hf eHGQc TGg (B((3WHbGJ CYjGf GdTjYI(B)s
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO MeO Gddg aGWQ PhGJ GdYbhd GdfhQjI heXgQ NajGJ GdCSQGQ (B... (3eaghe eTJQcG Hjf GdehLhOGJ acGf (B... (3GdCfhGY GdOGNdI ajY HYVgG Yf HYVs
(3BNQgG (B:s
(3BNQgG(B: (3hGdEeGe ceG PcQ aj GdeNdU CMhGd GdfaS HYO GdeYGQa hPcQ eG YdjgG hHGdLedI eYQaI GdCMhGd HYO Gddg YSQI dG jYdegG HGdMbjbI EdG Gddg SHMGfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B13: 129s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdadSaI hGdefWbs